Glioma-Derived Extracellular Vesicles – Far More Than Local Mediators - Tankov, Stoyan; Walker, Paul R. (Frontiers in Immunology, 2021)
Extracellular vesicle (EV) secretion is a ubiquitous cellular process with both physiologic and pathologic consequences. EVs are small lipid bilayer vesicles that encompass both microvesicles and exosomes and which are secreted by virtually all cells including cancer cells. In this review, we will focus on the roles of EVs in mediating the crosstalk between glioblastoma (GBM) cells and innate and adaptive immune cells and the potential impact on glioma progression. Glioma-derived EVs contain many bioactive cargoes that can broaden and amplify glioma cell mediated immunosuppressive functions and thereby contribute to shaping the tumor microenvironment. We will discuss evidence demonstrating that the low oxygen (hypoxia) microenvironment in the GBM microenvironment, in addition to cell-intrinsic effects, can affect intercellular communication through EV release, raising the possibility that properties of the tumor core can more widely impact the tumor microenvironment. Recent advances in glioma-derived EV research have shown their importance not only as message carriers, but also as mediators of immune escape, with the capacity to reprogram tumor infiltrating immune cells. Exploring EV function in cancer-immune crosstalk is therefore becoming an important research area, opening up opportunities to develop EV monitoring for mechanistic studies as well as novel diagnostic glioma biomarker applications. However, robust and reproducible EV analysis is not always routinely established, whether in research or in clinical settings. Taking into account the current state of the art in EV studies, we will discuss the challenges and opportunities for extending the many exciting findings in basic research to a better interpretation of glioma and its response to current and future immunotherapies.